A Pilot Study Investigating Changes in Capillary Hemodynamics and Its Modulation by Exercise in the APP-PS1 Alzheimer Mouse Model - Lu, Xuecong; Moeini, Mohammad; Li, Baoqiang; Lu, Yuankang; Damseh, Rafat; Pouliot, Philippe; Thorin, Éric; Lesage, Frédéric (Frontiers in Neuroscience, 2019)
Dysfunction in neurovascular coupling that results in a mismatch between cerebral blood flow and neuronal activity has been suggested to play a key role in the pathogenesis of Alzheimer’s disease (AD). Meanwhile, physical exercise is a powerful approach for maintaining cognitive health, and could play a preventive role against the progression of AD. Given the fundamental role of capillaries in the oxygen transport to tissue, our study aimed to characterize changes in capillary hemodynamics with AD and AD supplemented by exercise. Exploiting two-photon microscopy, intrinsic signal optical imaging and magnetic resonance imaging, we found hemodynamic alterations and lower vascular density with AD, reversed by exercise. We further observed that capillary properties were branch order dependent and that stimulation evoked changes were attenuated with AD but increased by exercise. Our study provides novel insights into cerebral microcirculatory disturbances with AD and the modulating role of voluntary exercise on these alterations.